An Evaluation of Firm Characteristics and Financial Performance of Listed Oil and Gas Companies in Nigeria (Acta Universitatis Danubius. Œconomica, 2022)
The study examined the effect of firm characteristics on the financial performance of Nigerian-listed oil and gas companies. The information was obtained from the indices report of twelve (12) oil and gas companies listed on the Nigerian Stock Exchange (NSE) market between the periods 2015 - 2019 which covers the period before and after the economic downturn experienced in Nigeria. The data collected were analyzed using the pool and cross-sectional data. Descriptive statistics were used to examine the characterization of variables while the pooled least square technique was used to investigate the empirical relationship of the variables. The regression result shows that about 69% of the variation in financial performance is explained by the independent variable of Firm Size, Financial Leverage, Ownership Impetrated and Firm Age. Apart from these variables, there are other factors responsible for the financial performance of listed oil and gas companies in Nigeria. The findings revealed that there is a negative relationship between Firm Size and Ownership Impetrated on financial performance, while Financial Leverage and Firm Age showed a positive relationship on the financial performance of listed oil and gas companies in Nigeria. Based on these findings, the study recommends that businesses adopt a culture of capitalising and reporting all expenditures on their products.